2013
DOI: 10.1007/s10903-013-9787-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Patient Characteristics and Symptomatology on Knowledge, Attitudes, and Beliefs Among Foreign-born Tuberculosis Cases in the US and Canada

Abstract: Foreign-born individuals represent the majority of TB cases in the US/Canada. Little is known about their TB knowledge, attitudes, and beliefs (KAB). Cross-sectional survey was conducted in 22 sites in the US/Canada among foreign-born adults with active TB. Multiple regression was used to examine KAB factors against covariates. Of 1,475 participants interviewed, most answered the six knowledge items correctly. Significant predictors of correct knowledge included region of origin, education, income, age, visa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
1
11
0
1
Order By: Relevance
“…An important demographic difference between the two groups was education: more than three-quarters of whites had at least a high school education, compared to <60 % of blacks. Other studies have found that less formal education is associated with poorer understanding of TB [11, 21]. In this study, blacks were more likely to say that they did not have enough information about TB.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…An important demographic difference between the two groups was education: more than three-quarters of whites had at least a high school education, compared to <60 % of blacks. Other studies have found that less formal education is associated with poorer understanding of TB [11, 21]. In this study, blacks were more likely to say that they did not have enough information about TB.…”
Section: Discussionmentioning
confidence: 61%
“…The influence of knowledge on changing a person's behaviors is well recognized; in particular, increasing TB knowledge has been associated with healthy behaviors and more favorable outcomes for TB patients [11–19]. This is the first study that compared TB knowledge and attitudes between U.S.-born black and white TB patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations